Kepenyairan A. Mustofa Bisri Berangkat dari Ajaran al KKeeppeennyyaaiirraann AA.. MMuussttooffaa BBiissrrii BBeerraannggkkaatt ddaarrii AAjjaarraann al al Kepenyairan A. Mustofa Bisri Berangkat dari Ajaran al- -- - Qur’an dan al QQuurr’’aann ddaan - abdul wachid (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
We know that A. Mustofa Bisri is an Islamic spiritualist. Of course, everything Sufi do never â€œexhibitedâ€ by A. Mustofa Bisri, because â€œritual pious and social piousâ€ unified, and value of someoneâ€™s ibadah (ritual) to Allah measured by his ikhlas. However, from poem, short stories, and essay he writes, clearly presenting interpretation and realization of his life view that suggested y al-Qurâ€™an and al-Hadis. A. Mustofa Bisri writing everything based on spiritual motive, delivering hikmah (wisdom), and finding lifeâ€™s blessing. He believes that high quality art work can wake up love that sleeps inside heart, meaning worldly love or God love.